2013
DOI: 10.1111/tpj.12395
|View full text |Cite
|
Sign up to set email alerts
|

Reduced phototropism in pks mutants may be due to altered auxin‐regulated gene expression or reduced lateral auxin transport

Abstract: SUMMARYPhototropism allows plants to orient their photosynthetic organs towards the light. In Arabidopsis, phototropins 1 and 2 sense directional blue light such that phot1 triggers phototropism in response to low fluence rates, while both phot1 and phot2 mediate this response under higher light conditions. Phototropism results from asymmetric growth in the hypocotyl elongation zone that depends on an auxin gradient across the embryonic stem. How phototropin activation leads to this growth response is still po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(64 citation statements)
references
References 48 publications
4
59
0
Order By: Relevance
“…In addition to ABCB19, members of the Phytochrome Kinase Substrate (PKS) family have also been shown to play a role in phototropism. PKS4 is rapidly phosphorylated by phot1 in response to blue light and is proposed to impact phototropism positively or negatively depending on its phosphorylation status (Demarsy et al 2012, Kami et al 2014). The biochemical function of PKS proteins is presently unknown, but they probably impact auxin signaling or transport (Kami et al 2014).…”
Section: Phototropinsmentioning
confidence: 99%
“…In addition to ABCB19, members of the Phytochrome Kinase Substrate (PKS) family have also been shown to play a role in phototropism. PKS4 is rapidly phosphorylated by phot1 in response to blue light and is proposed to impact phototropism positively or negatively depending on its phosphorylation status (Demarsy et al 2012, Kami et al 2014). The biochemical function of PKS proteins is presently unknown, but they probably impact auxin signaling or transport (Kami et al 2014).…”
Section: Phototropinsmentioning
confidence: 99%
“…While PKS proteins are required for phytochrome signaling (Lariguet et al, 2003;Schepens et al, 2008), some of the phenotypes associated with pks mutants resemble those of nph3, rpt2, and phot-deficient mutants. For instance, the pks1 pks2 pks4 triple mutant exhibits reduced phototropic curvature (Lariguet et al, 2006;Kami et al, 2014). PKS1 and PKS2 also act in concert with NPH3 to establish leaf positioning and leaf expansion (de Carbonnel et al, 2010).…”
Section: Phytochrome Kinase Substrate Proteinsmentioning
confidence: 99%
“…Resolving the biochemical functions of these proteins and how they integrate with NPH3 and RPT2 will be important to fully understand how phots initiate signaling from the plasma membrane. Like NPH3, PKS proteins are suggested to modulate auxin transport or signaling (de Carbonnel et al, 2010;Kami et al, 2014). Yet, their mechanism of action in this regard remains to be elucidated.…”
Section: Phytochrome Kinase Substrate Proteinsmentioning
confidence: 99%
“…Several studies have demonstrated that PKSs serve as a molecular link between phytochrome and phototropin-mediated responses through interaction with phytochromes and PHOT1 (Lariguet et al, 2006; Demarsy et al, 2012; Kami et al, 2014). PKSs may contribute to the phototropic response regulation through modulation of local auxin signaling or transport (Kami et al, 2014). Hence, light can effectively coordinate the activity of major auxin transporters and therefore auxin distribution to control phototropic responses in different organs (Žádníková et al, 2015).…”
Section: Discussionmentioning
confidence: 99%